ChemInform Abstract: 3‐P=O‐Functionalized Phospholane 1‐Oxides by the Michael Reaction of 1‐Phenyl‐2‐phospholene 1‐Oxide and Dialkyl Phosphites, H‐Phosphinates, or Diphenylphosphine Oxide. Issue 12 (14th March 2013) - Jablonkai, Erzsebet; Drahos, Laszlo; Drzazga, Zbigniew; Pietrusiewicz, K. Michal; Keglevich, Gyoergy
Abstract The reaction proceeds better under conventional conditions.